(untitled) (The Conference Hub, 2025)
This article examines grammatical competence as one of the fundamental components of foreign language teaching. It analyzes the essence and role of grammatical competence in the process of mastering a foreign language, emphasizing its significance for the development of communicative skills, linguistic awareness, and the ability to construct correct and meaningful utterances. The study also highlights the interrelation between grammatical competence and other aspects of language learning, such as lexical, phonetic, and pragmatic competencies.